(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Objectives Survey about numbers of students and employers that they were influenced by recurrent using of computers and smart devices, in addition to that, the comparative study performing by knowing of relationship with different and effect on them. Materials And Methods This study was executed on individuals of students and employees during 1 year only (from January 1st 2016 to August 15th 2017) in the College of Health and Medical Technology /kufa in the province of Al-Najaf. It is included in the relation between frequent using of computers and smart devices and another risk factor. Results The results shown significant differences in student’s users of computers and smart devices in which there were little numbers of visions influencing among them in different ages and genders. Utilizing for long periods during days in different purposes yet didn’t have a greater effect on users in case of computer vision syndrome according to the employer’s users. Since the preparation of students was having medical glass in male and female and the letter has rated more than the male. In another hand the ages at about (24-32) the using of computers and smart devices was, and the more risk factors among all of them had had greater rates of correlation with the glass wearing in a group of students that they have eye allergy in comparison with the time user. Also these results were shown the superiority of male in comparison with female in using these devices So, from the results mentioned above the convergence in numbers of students that they have vision affects due to employment of these devices in such of ages about [(19-23), (24-32)] in male and female, but the first ages have slightly higher rates than other)] by percentage (50%) of the students that suffer from computer vision syndrome from all proportion, whereas 2nd group of another age has low significant differences in comparison with previous by the percentage closely (36.36%). The employer’s users of computer and smart devices have significant differences (p< 0.05) from the previous results, where it was noticed large numbers of users suffer from problems in their vision due to profuse utilization for long periods of this advice. At the ages (31-40) using for different purposes whether (science, entertaining or both of them) has close correlation with hitting of employers by vision syndrome, where this factor has significant differences in comparison with other risks (p<0.05), while utilizing of these devices under different lights numbers appeared to affect lower than it , also these results were shown no significant differences with regard to employer’s users that they were utilized optical glass after they had using these devices, also effect of this factor ( light numbers) on the putting of eyeglass and presence of significant differences (p<0.05) in comparison with the individuals of users that laying screen protection . We found significant differences (p< 0.05) in numbers of employers were wearing eyeglass after utilizing these appliances and these demonstrate the vulnerability of devices users and the percentage was (58.14%). Conclusions : Using computers and smart devices of students more than employers. Appearing different ienfluencing of eye glass wearing of students and employers that utilizing different computers and smart devices with some of risk factors according to others. It is Found assuring correlations among different risk factors , but shown in employers greater than students.